Comparative Analysis of Biodiesel Produced from Blends of Palm Kernel Shell and Cocoa Pods Oils with Conventional Diesel Fuel: Characterizations, FTIR, GC-MS, XRD and SEM Analysis of the Nano Catalyst - Nkanang, Bassey; Abam, Fidelis; Ndukwu, Macmanus; Ugwu, Hyginus; Oboh, Agnes (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
The uncertainty of predicting the conditions of bio oils for the production of quality biofuels and reusability of catalyst, saving cost of production and time, make characterization of the oils/catalyst imperative. Characterization of bio oils, extracted from palm kernel shell and cocoa pods, the blends, catalyst and biodiesel produced therefrom is investigated. A maximum biodiesel yield of 76.05% was obtained at optimal conditions. Titanuim oxide used proved to be efficient catalyst for converting the oil blends to biodiesel. The established results obtained show kinematic viscosity of 5.65 – 7.78 mm2s-1 @ 40 oC, density of 0.8428 – 0.8642 kg/m3, cloud point of 4.48 – 6.48 oC, fire point of 108 – 150 oC, cetane index of 37.78 – 30.13, acid value of mg KOH/g, API gravity of 32.89 – 29, anicidine point of 50 – 46 oC etc. All the values fell within the recommended ASTM and EN standards. The GC-MS, XRD, EDX, SEM, and FTIR analyses carried out to evaluate the quality of the sample with respect to deterioration, gave an ester percentage of 99.9% for the bio-oil and biodiesel, which is within the minimum standard range of not less than 96.5% recommended. The GC-MS of the blended oil shows that the most prevalent fatty acids identified amongst 13 other distinct compounds were methyl linolenate, methyl palmitate, methyl oleate and methyl eicosadinoate with percentage concentrations of 63.03, 26.9, 8.1 and 2% respectively. The XRD analysis confirmed the titanium oxide anatase structure with a peak of 25.4 degrees. The SEM analysis shows high porosity with high specific surface area of the catalyst at magnification of 80 – 269μm; and the FTIR analysis revealed that the functional groups for the bio-oil and blended biodiesel were in range.